2018
DOI: 10.1371/journal.pone.0200140
|View full text |Cite
|
Sign up to set email alerts
|

Association of current and former smoking with body mass index: A study of smoking discordant twin pairs from 21 twin cohorts

Abstract: BackgroundSmokers tend to weigh less than never smokers, while successful quitting leads to an increase in body weight. Because smokers and non-smokers may differ in genetic and environmental family background, we analysed data from twin pairs in which the co-twins differed by their smoking behaviour to evaluate if the association between smoking and body mass index (BMI) remains after controlling for family background.Methods and findingsThe international CODATwins database includes information on smoking and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 46 publications
3
49
1
Order By: Relevance
“…Epidemiological studies have suggested that smoking is associated with lower BMI (Audrain-McGovern and Benowitz, 2011). A large international twin study found that a similar association can also been found in smoking discordant pairs when a smoking co-twin has, on average, lower BMI than a never smoking co-twin (Piirtola et al, 2018). This provides further evidence that smoking is causally associated with reduced BMI.…”
Section: Experimental and Discordant Pair Twin Studiessupporting
confidence: 52%
“…Epidemiological studies have suggested that smoking is associated with lower BMI (Audrain-McGovern and Benowitz, 2011). A large international twin study found that a similar association can also been found in smoking discordant pairs when a smoking co-twin has, on average, lower BMI than a never smoking co-twin (Piirtola et al, 2018). This provides further evidence that smoking is causally associated with reduced BMI.…”
Section: Experimental and Discordant Pair Twin Studiessupporting
confidence: 52%
“…More so, the impact of marriage on overweight and obesity could be as a result of women’s sexual and reproductive activities such as child bearing with increase in sedentary lifestyles. The content of alcohol or “hot drinks” and nicotine obtain from smoking, especially for heavy users could be responsible for the breakdown of body cells leading to reduction in the risk of overweight and obesity as found in this study [ 30 , 31 ]. Notwithstanding, smoking and alcohol consumption are known to have negative long-term health effect to the body.…”
Section: Discussionmentioning
confidence: 85%
“…However, for UC, in whom smoking is protective, the risk decreased with increasing BMI, which is counter to what would be expected if smoking behavior was an influence on low BMI in this cohort. Other current evidence speaks against a strong association between smoking and BMI in young adulthood 19 . The Surgeon General’s report 20 indicated that for smokers aged 18 or younger, BMI was the same or higher in smokers, with reductions in BMI only emerging after the age of 35.…”
Section: Discussionmentioning
confidence: 87%